The Effect of Leadership, Physical Work Environment, and Work Discipline on the Performance of Production Department Employees at PT Widaya Inti Plasma - Devi Putri Ayu Febrianti; Bowo Santoso (Politeknik Negeri Bengkalis, 2023)
The organization is a complex unit that seeks to allocate human resources in full to achieve goals. This study aims to analyze the effect of leadership, physical work environment, and work discipline on the performance of production employees at PT Widaya Inti Plasma. The research method used in this research is quantitative research with the type of explanatory research. This study uses the independent variables namely Leadership, Physical Work Environment, Work Discipline and the dependent variable namely Employee Performance. Withdrawal of samples using probability sampling method with simple random sampling technique. The implementation of this simple random sampling is due to the very large population and the sample taken is a homogeneous population, namely employees of the production division of PT Widaya Inti Plasma. With a margin of error of 10%, it can be seen that the number of respondents set is 70 employees in the production department of PT Widaya Inti Plasma. The results of this study indicate that good leadership carried out by PT Widaya Inti Plasma can improve the performance of production employees at PT Widaya Inti Plasma. Then a comfortable and good physical work environment can improve the performance of production employees at PT Widaya Inti Plasma. As well as the better work discipline for employees, the performance of employees at PT Widaya Inti Plasma will be maximized and meet the targets that have been set.